ANALISIS PENGARUH FUND AGE, MARKET TIMING ABILITY, STOCK SELECTION SKILL, PORTFOLIO TURNOVER DAN FUND SIZE TERHADAP KINERJA REKSA DANA SYARIAH PERIODE 2013 - 2015 - Wicaksono, Muhammad Pambudi; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2017)
Mutual funds is one means of investment consisting of a collection of funds obtained from various investors to be invested in securities portfolio by the investment manager. Sharia mutual funds are mutual funds whose operations are based on Islamic sharia principles. This study aims to analyze the influence of fund age, market timing ability, stock selection skill, portfolio turnover and fund size to the performance of Islamic mutual funds in Indonesia. The method used is multiple regression analysis with classical assumption test as statistical requirement. The data used in this study consist of monthly NAV data, effective date of mutual fund, mutual fund financial report, SBIS and JCI in the period 2013-2015. The sample is divided according to the purpose of investment consisting of 8 sharia equity funds, 7 sharia balanced funds and 3 sharia fixed income funds. The results showed that simultaneously fund age character, market timing ability, stock selection skill, portfolio turnover and fund size influence sharia mutual fund performance by 19%. In partial test, it is found that fund age has negative and insignificant effect on sharia mutual fund performance. Market timing ability and portfolio turnover have positive and insignificant effect on sharia mutual fund performance. Stock selection skill and fund size have a positive and significant effect on sharia mutual fund performance.